The association between early child environment and children's outcomes: evidence from the Birth to Twenty Plus study - Cele, Refiloe Lerato (My University, 2017)
Later adult outcomes in health, economic participation and psychological well-being have been scientifically linked to early childhood development. Thus, it is paramount that children be exposed to nurturing environments that optimise their development, especially for those who are most vulnerable. We investigated the effects of early child care quality (in-and out-of-home) as a proximal early child environmental factor at the ages of six months to two years, and again later at the ages of four to five years on children’s cognitive development and schooling outcomes, using data from the South African Birth to Twenty Plus cohort. The Revised Denver Pre-screening Developmental Questionnaire (R-DPDQ) was used as a measure of cognitive development at five years of age and the number of grade repeats by Grade 7 was used to measure schooling achievement. The sample size differed by outcome, age category and environment analysed. The final analytical sample varied from 203 to 1148 children. Our measures of in-home quality of care at six months to two years was a latent variable of quality child care, which was created by combining cognitive stimulation scores and maternal responsiveness scores. At the ages of four to five years, measures of in-home quality of care included child supervision and cognitive stimulation. Measures of child care quality in the out-of-home environment included childminder education at the ages of six months to two years, number of children in the care of the childminder at the ages of six months to two years and at the ages of four to five years, and the type of daycare/crèche attended at the ages of four to five years. To assess the impact of in-and out-of-home child care quality on cognitive functioning, multivariate linear regressions were estimated. To assess the impact of in-and out-of-home child care quality on schooling achievement, multivariate logistic regression analysis was conducted. Our findings showed that children who received high quality child care in the home, as indexed by high maternal responsiveness and high cognitive stimulation between the ages of six months and two years, scored 1.3 points higher in the R-DPDQ at the age of five years, compared to children who received low quality care (β = 1.25, p<0.01, 95% CI: 0.49, 2.01). High maternal responsiveness scores between the ages of six months and two years were protective against the risk of grade repetition in primary school (OR = 0.95, p<0.05, 95% CI: 0.90, 0.99). The analysis of the out-of-home environment revealed that children between the ages of six months and two years who had childminders with post-school training, scored 4 points higher in the R-DPDQ (β = 3.91, p<0.05, 95% CI: 0.05, 7.76) compared to children with childminders who had a Grade 7 education level or lower. Children between the ages of six months and two years who had childminders with an education level of Grade 11 or Grade 12 had a 57% lower chance of repeating a grade (OR = 0.43, p<0.05, 95% CI: 0.17, 0.99) by Grade 7, compared to children whose childminders had a Grade 7 education level or lower. Children between the ages of six months and two years who were cared for in small group sizes (less than six children per group) had a 65% reduction in the odds ratio for repeating a grade (OR = 0.35, p<0.05, 95% CI: 0.13, 0.94) by Grade 7, compared to children who were cared for in groups of seven or more. There was also evidence that the children from lower socioeconomic backgrounds who received high quality child care, both in-and out- of the home, scored higher in the R-DPDQ compared to children of the same socioeconomic status who received lower quality care. Children under the age of two years in the low socioeconomic status group receiving high quality child care in the home scored 2 points higher on the R-DPDQ at age five years compared to children receiving low quality care in the same socioeconomic status group (β = 1.99, p<0.05, 95% CI: 0.45, 3.51). Furthermore, low socioeconomic status children under the age of two years who were had out-of-home care either in the sole care of a childminder (β = 11.55, p<0.01, 95% CI: 4.82, 18.27) or in a group of fewer than six children (β = 12.41, p<0.01, 95% CI: 5.71, 19.11) scored 12 points higher in the R-DPDQ at the age of five years, compared to children cared for in big groups (seven to 50 children) in the same socioeconomic status category. High quality child care environments, both in-and out-of-home, were positively associated with young children’s cognitive and schooling outcomes in this study. However, the strength of this association was attenuated by household socioeconomic status and maternal education. Thus, strategies and policies aimed at improving children’s socioeconomic conditions and child care quality within the home, and in out-of-home early child care as well as in education settings will have lasting positive effects, especially for young children living in poverty.
A dissertation submitted to the Faculty of Health Sciences, Department of Paediatrics, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2017.
Keywords: Early Childhood Development; Cognitive Development (Learning Disorders)